Vocational Students’ Perception towards Learning English through Social Media - Rizki Muhammad Ardian Setiadi; Mila Rosmaya (Indonesian Journal of ELT and Applied Linguistics, 2024)
This study investigates vocational students' perceptions of using social media as a tool for learning English. With the increasing prevalence of social media platforms in students' daily lives, their potential in supporting language acquisition has become a relevant subject of inquiry. This research employs a descriptive qualitative approach, using a structured questionnaire with a 4-point Likert scale to gather data from 114 vocational high school students. The results show that students view social media positively in terms of its contribution to improving their English learning. Respondents reported that social media platforms make learning more enjoyable, reduce anxiety, boost confidence, and foster independent learning. Students also perceived improvements in core language skills—listening, speaking, reading, and writing—as well as vocabulary, pronunciation, and grammar. However, the study also identified challenges, including exposure to inappropriate content, privacy concerns, and limited internet access. These findings emphasize the need for digital literacy and proper guidance to fully leverage the educational advantages of social media. The study concludes that, with suitable teaching approaches and awareness of possible drawbacks, social media serves as an effective supplementary resource for vocational students learning English.